PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN PENDEKATAN CTL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIA SMP NEGERI 18 PEKANBARU - Fitri, Del; ', Zulkarnain; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on study results of mathematics subject fromclass VIIIA SMP 18 Pekanbaru which still under KKM assigned by school that is 75. The purpose of this research is to improve the learning process and improve achievement of learning mathematic by implementation of cooperative learning model type STAD with CTL approach. This research is a class action research of two cycle. Subject researchers were the students in the class VIIIA of SMP Negeri 18 Pekanbaru that consist of 20 boys and 20 girls at second semester of academic year 2015/2016. From the results of annalysis found that the learning process improvements of learning process prior to the action on the first and second cycles. The results of this research showed an increasing number of students learning mathematic from the basic score with percentage 45% to 63% on the first test and 73% on second test. Based on the result of this research could be concluded that the implementation of cooperative learning model type STAD with CTL approachcan improve the learning process and improve the achievement of learning mathematic in class VIIIA of SMP Negeri 18 Pekanbaru in second semester academic years 2015/2016.